1978
DOI: 10.1021/ja00477a031
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen binding to cobalt porphyrins

Abstract: The thermodynamic constants of oxygen binding to cobalt "picket fence" porphyrin complexes, mejo-tetra(a,a,a,ao-pivalamidophenyl)porphyrinatocobalt(II)-1 -methylimidazole and 1,2-dimethylimidazole, are reported. In contrast to previously studied cobalt porphyrins, these complexes bind oxygen with the same affinity as cobalt substituted myoglobin and hemoglobin. Solvation effects are discussed as the source of this difference. The use of sterically hindered axial bases as models of T state hemoglobin is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
137
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 12 publications
5
137
0
Order By: Relevance
“…[2] Those investigations showed that an additional electron donating ligand so-called 'axial ligand' is essential for efficient binding of oxygen. Later investigations revealed that reversible oxygenation behavior is not confined to Co(II) complexes of salicylaldimine, but many other Co(II) complexes such as ethylenediamine-bridged bis-β-diketones, [3] porphyrins, [4] and cyclams [5] can bind molecular oxygen to give 1:1 or 2:1 oxygen adducts depending on nature [6] and steric effects [7] of the ligating groups.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Those investigations showed that an additional electron donating ligand so-called 'axial ligand' is essential for efficient binding of oxygen. Later investigations revealed that reversible oxygenation behavior is not confined to Co(II) complexes of salicylaldimine, but many other Co(II) complexes such as ethylenediamine-bridged bis-β-diketones, [3] porphyrins, [4] and cyclams [5] can bind molecular oxygen to give 1:1 or 2:1 oxygen adducts depending on nature [6] and steric effects [7] of the ligating groups.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins appear particularly attractive for this purpose [16], as they stabilize the diamagnetic cobalt(III) center and prevent undesired redox-processes at the metal [17]. In addition, coordination of a NHC leaves one labile coordination site opposite to the carbene, which should eventually allow the strong trans effect of the NHC ligand to be exploited.…”
Section: Introductionmentioning
confidence: 99%
“…1 Our interest in this area goes back some 30 years to our studies of reversible O 2 binding in porous molecular solids of picket-fence metalloporphyrins [2][3][4] and especially our adventitious discovery of cooperativity in such binding for several such solids. 5,6 Planning and prediction of the structures of molecular solids, however, is notoriously difficult.…”
Section: Introductionmentioning
confidence: 99%